Cenozoic tectonic evolution of South China: A brief review, and new insights from the Huangshadong‐Shiba area, south‐east China. (21st June 2020) - Kuang, Jian; Wang, Shuai; Qi, Shihua; Xiao, Zhicai; Zhang, Min; Wang, Yousheng
Abstract : The Cenozoic tectonic dynamic process controlled by the Pacific subduction and Tethyan subduction/collision in South China are still controversial and lacks geological evidence of intracontinental deformation to define. Here, we focused on the Huangshadong‐Shiba area (HSA) in the south‐eastern coastal area of China. This study aims to obtain multi‐stage geological events by an integrated multidisciplinary investigation to decipher the multiple tectonic deformation in Cenozoic South China. We found that the Jurassic and Cretaceous granite not only dominates in surface magmatic rocks but also integrates into a whole with buried depth more than 2 km. This plate‐like granite (it means the occurrence of granite is like a tremendous plate) with thickness more than 3 km is sliced by Heyuan Fault, Renzishi Fault, and Zijin‐Boluo Fault. The basalts in the Shiba Basin have an Ocean Island Basalt‐like property, and the Heyuan Fault controlled the distribution of basalt. Our results, merged with a review of the Cenozoic tectonic evolution in South China, emphasise the decisive role of the India–Eurasia collision on the tectonics of South China in the Palaeogene and suggest the continuous northward drift of the Philippine Sea Plate and Australian Plate had a substantial effect on South China in the Neogene. This study also proposes a two‐stage tectonic activity model to visualise the Cenozoic tectonic activity acting on the HSA or South China.